2012
DOI: 10.3109/02713683.2012.674610
|View full text |Cite|
|
Sign up to set email alerts
|

Measurement of Dynamic Ocular Surface Temperature in Healthy Subjects Using a New Thermography Device

Abstract: Ocular surface temperature measurements made using the Tomey TG 1000 in healthy subjects showed excellent intraobserver reproducibility. This novel non-invasive technique offers new options for increased understanding of the physiology of the ocular surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1
2

Year Published

2012
2012
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 20 publications
0
22
1
2
Order By: Relevance
“…However, our OST was specially designed for the ocular surface and can measure the temperature more accurately and with greater sensitivity [13]. Furthermore, the ocular surface temperature measured by the OST has been reported to be highly reproducible [30]. The differences in the instruments may be the reason for the differences between the findings of Rimas et al and our study.…”
Section: Discussioncontrasting
confidence: 57%
“…However, our OST was specially designed for the ocular surface and can measure the temperature more accurately and with greater sensitivity [13]. Furthermore, the ocular surface temperature measured by the OST has been reported to be highly reproducible [30]. The differences in the instruments may be the reason for the differences between the findings of Rimas et al and our study.…”
Section: Discussioncontrasting
confidence: 57%
“…OST measurement has been applied to dry eye disease [8][9][10][11][12], contact lens wear [13,14], laser refractive surgery, infectious eye disease and others [15][16][17][18][19][20]. Nevertheless, to the best of our knowledge, the impact of corneal thickness (CT), endothelial cell density (ECD) anterior chamber depth (ACD) on ocular surface temperature (OST) has not been investigated, yet.…”
Section: Introductionmentioning
confidence: 95%
“…Kamao et al [14] first described this ocular surface thermographer. In a previous study we indicated a high reproducibility in ocular surface temperature measurements taken with this instrument [15]. The instrument is equipped with an infrared camera module (HX083M1; NEC, Tokyo, Japan) and a color charge-coupled device onboard camera (PKD-101; Pacific Corp., Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%